2015
DOI: 10.1074/jbc.m115.675538
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Dissection of the Pre-existing Conformational Equilibrium in the Trypsin Fold

Abstract: Background:The pre-existing equilibrium between open (E*) and closed (E) conformations is a defining feature of the trypsin fold, but its kinetic signatures remain elusive. Results: Kinetics of the E*-E interconversion are determined for protease and zymogen. Conclusion: Protease and zymogen differ in the relative distribution of E* and E. Significance: The role of the E*-E equilibrium in the trypsin fold is elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 87 publications
(107 reference statements)
10
58
0
Order By: Relevance
“…In factor Xa, the presence of three consecutive serines (171-173) may mitigate the mobility of the water network (48), leading to higher intrinsic activity of this protease (53). In thrombin, recent work has shown that the apo form of thrombin is highly flexible (17) and exists in an open/ collapsed equilibrium controlled by the position of the 215-217 segment (16,18,54) where the addition of Na ϩ shifts the equilibrium in favor of the open form. We speculate that in the apo form the water network in thrombin facilitates a 170 loop-mediated stabilization of segment 215-217.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In factor Xa, the presence of three consecutive serines (171-173) may mitigate the mobility of the water network (48), leading to higher intrinsic activity of this protease (53). In thrombin, recent work has shown that the apo form of thrombin is highly flexible (17) and exists in an open/ collapsed equilibrium controlled by the position of the 215-217 segment (16,18,54) where the addition of Na ϩ shifts the equilibrium in favor of the open form. We speculate that in the apo form the water network in thrombin facilitates a 170 loop-mediated stabilization of segment 215-217.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FVIIa-Y T displays a similar extent of N terminus insertion as FVIIa wild type (WT) in the absence of TF; however, FVIIa-Y T displays improved catalytic efficiency. Recent studies with thrombin, another trypsin-like serine protease, reveal a highly plastic protease fold for the apo form of thrombin that undergoes structural transitions upon cofactor binding (13)(14)(15)(16)(17)(18)(19). In particular, segment 215-217 was shown to be vital for substrate access and cofactor-mediated allosteric regulation, which may also be the case in TF-mediated allosteric regulation of FVIIa activity (20,21).…”
mentioning
confidence: 99%
“…6) suggests that HABP2 G221E lacks the stabilization of the S1 pocket that normally results from N terminus insertion. As such, the activated form of HABP2 G221E may predominantly be inactive, presumably because of a shift of the equilibrium between closed (E*) and open (E) forms (23) or in the continuum between zymogen-and proteinase-like states (24).…”
Section: Hydrolysis Of S-2288mentioning
confidence: 99%
“…For the different zymogens, the pre-existing E 7 E* equilibrium is variably shifted to the E* form with equilibrium constants (K eq ) ranging from 10 8 (trypsinogen) (12) to 7 (tissue plasminogen activator) (13). For Pre2, a K eq of 10 has been recently determined (14). An indirect, albeit stringent, proof of the existence of the E 7 E* equilibrium in ProT is that protein binding to thrombin precursors can effectively stabilize the active E form, as demonstrated in the case of staphylocoagulase (SC) (15) and von Willebrand factor-binding protein (vWbp) (10), two proteins secreted from the virulent Gram-positive bacterium Staphylococcus aureus exploiting a molecular mimicry mechanism to orient their N-terminal Ile-1-Val-2 dipeptide into the Asp-524 cavity, thus leading to non-proteolytic activation of ProT.…”
mentioning
confidence: 99%